Sumienie. Aspekty psychologiczne i pedagogiczne - Hanisch, Helmut (Horyzonty Wychowania, 2017)
The author ponders over one of the main anthropological issues concerning the process of man’s upbringing, namely the possibilities of educating human conscience. Three psychological concepts: Sigmund Freud’s psychoanalysis, Carl Gustav Jung’s neopsychoanalysis and Philip Lersch’s personality psychology formed the background to his pedagogical reflections. The presentation of each scholar’s views ends with a conclusion formulated on the basis of the question about the possibility to infer the foundations (also axiological) for a particular pedagogy from a given psychological conception. The closest to the author and also, in his opinion, the most fruitful for the process of upbringing is Philip Lersch’s concept emphasizing the role of the experience of sense in the formation of human conscience. In order to develop and deepen this direction of deliberations, the author refers to Eric Erickson’s concept, for which the key moment linking experiencing the world and building this feeling of sense is prime confidence. In the last part of the study the author, searching for a broader axiological horizon conditioning the formation of conscience, refers to a transcendent perspective, possible to express also in religious values. For the upbringing process, however, conscience has the fundamental meaning, not so much the „transmoral- religious” as „moral-ethic conscience”, which „operates” only when it is accompanied by a deep sense of obligation to particular values, and also joy and pleasure resulting from fulfilling them.